(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This research paper explores the relationship between work-life balance, mindfulness, and work engagement among Employees. By analyzing quantitative and qualitative data from 150 Employees across various industries, this study aims to understand how these factors influence commitment, enthusiasm, and overall performance at work.